Near-optimal Bayesian localization via incoherence and sparsity - Cevher, Volkan; Boufounos, Petros; Baraniuk, Richard G.; Gilbert, Anna C.; Strauss, Martin J. (2009 International Conference on Information Processing in Sensor Networks, 2009)
This paper exploits recent developments in sparse approximation and compressive sensing to efficiently perform localization in a sensor network. We introduce a Bayesian framework for the localization problem and provide sparse approximations to its optimal solution. By exploiting the spatial sparsity of the posterior density, we demonstrate that the optimal solution can be computed using fast sparse approximation algorithms. We show that exploiting the signal sparsity can reduce the sensing and computational cost on the sensors, as well as the communication bandwidth. We further illustrate that the sparsity of the source locations can be exploited to decentralize the computation of the source locations and reduce the sensor communications even further. We also discuss how recent results in 1-bit compressive sensing can significantly reduce the amount of inter-sensor communications by transmitting only the intrinsic timing information. Finally, we develop a computationally efficient algorithm for bearing estimation using a network of sensors with provable guarantees.